Impact of underlying diabetes and presence of lung cavities on treatment outcomes in patients with pulmonary tuberculosis. Issue 6 (13th March 2014) - Nakamura, A.; Hagiwara, E.; Hamai, J.; Taguri, M.; Terauchi, Y.
Abstract Aims We investigated the effects of diabetes and the presence of lung cavities on treatment outcomes in patients with pulmonary tuberculosis. Methods We conducted a retrospective review of the clinical records of all consecutive patients admitted to the Kanagawa Cardiovascular and Respiratory Centre with the diagnosis of pulmonary tuberculosis. The study outcomes examined were time to sputum culture conversion and percentage of patients with sputum culture conversion by the time 2 months of treatment, and these outcomes were compared between patients with and without diabetes. Results Of the 260 patients enrolled in the study, 69 were diagnosed as having diabetes mellitus, while the remaining 191 did not have diabetes. The percentage of patients with cavities was higher in the patients with diabetes (71.0%) than in those without (45.5%; P = 0.0003). The time to sputum culture conversion was significantly longer in the patients with diabetes than in those without (P = 0.0005), and the percentage of patients with a positive sputum culture at 2 months was higher in the patients with diabetes (43.5%) than in those without (18.8%; P = 0.0001). Multivariate analyses revealed that the presence/absence of lung cavities was a more important determinant of treatment outcomes than the presence/absence of diabetes. Conclusions The presence of lung cavities was found to be a more important determinant of the treatment outcomes than that of diabetes per se in patients with pulmonary tuberculosis.